Analisis Penyebab Pengusaha Peron Kelapa Sawit Tidak Membayar Zakat Di Kecamatan Tigo Nagari Kabupaten Pasaman Perspektif Ekonomi Islam - Asrul Gustomi; Rizal Fahlefi; Nil Firdaus (Al-Hisbah Jurnal Ekonomi Syariah, 2025)
This study aims to analyze the factors causing palm oil platform entrepreneurs not to pay zakat from an Islamic economic perspective, analyze the obstacles and challenges of palm oil platform entrepreneurs in paying zakat and to describe how religious leaders socialize the importance of paying zakat in palm oil platform businesses. This study was conducted on Palm Oil Platform entrepreneurs in Tigo Nagari District, Pasaman Regency. This type of research is field research with a qualitative approach. Data sources in this study are primary data sources and secondary data sources. The techniques used in data collection are observation, interviews and documentation. The techniques for analyzing data in this study are data reduction, data presentation and conclusions. The techniques for guaranteeing the validity of data in this study are source triangulation and time triangulation. The results of this study reveal that the factors causing palm oil platform entrepreneurs in Tigo Nagari District, Pasaman Regency not to pay zakat are understanding, low trust in amil zakat, excessive lifestyle, religiosity, social environment and the absence of sanctions by the government. Obstacles and challenges in the palm oil platform business are caused by unstable palm oil harvests and price fluctuations, difficulties in financial record-keeping, and high competition among platform owners. Religious leaders have been promoting the importance of paying zakat for palm oil platform businesses by visiting the homes of platform owners and holding lectures and religious studies.